Ex-votos e poiesis: representações simbólicas na fé e na arte - Duarte, Ana Helena da Silva Delfino (2011)
The thesis "Ex-votos and Poiesis: symbolic representations of faith and art" attempts to analyze the votive images that are popular representations of the Catholic faith, and that are embodied in pictorial panels, sculptural objects, photographs and other everyday "mere things" objects, re-signified in ex-votos, and exposed in promise rooms. Through the iconography of these objects we tried to interpret their religious, artistic, semiotic, historical, anthropological and ethnographic meanings, considering the networks involved: requests, promises, pilgrimages, payments and various forms of thanking graces, and miracles achieved by divine intersection The sanctuary of Nossa Senhora Aparecida/SP have been chosen to host the research, focusing the ex-votes left in the sanctuary promises rooms; from that sacred space, which staged the empirical findings, we also investigated several other ex-votos left in promise rooms thorough Brazil and abroad. Some progress has been also made from the works of artists that allow the view of crossings, points of meeting and a dialogue between the current "institutionalized" art and the art of "miracles." Having these collections as the fulcrum of ex-votive faith, dialogues can be traced toward religion, and art and culture, noting the cultural circularity between the "popular and the scholar", the "lifestyles", and the religious social changes reflected in the ex-votes non-verbal imagery. Following the investigation of these objects, we tried to see them "inside and outside". We managed to consider and appease the vast majority of the questions that these iconic objects advocate. Thus, we find that almost anything, a priori, could be an ex-voto